Design of Smart Hydroponics Based on Internet of Things (IoT) Using Rule-Based System on Hydroponic Wick System - Prasetyoaji, Mukhamad Rio Eka; Anifah, Lilik (Journal FORTEI-JEERI, 2025)
This research develops an IoT-based intelligent hydroponic system to monitor and control nutrient and pH levels in wick-type hydroponic cultivation. The system uses an ESP32 microcontroller integrated with an MQTT-based IoT platform for real-time monitoring and automation. The rule-based system classifies plant conditions and controls actuators based on pH and nutrient levels. Experimental testing shows that the TDS and pH sensors work well. Using the two-factor correction method, the TDS sensor achieved high accuracy with a maximum error of 0.08% within the optimal range of 1,050-1,400 ppm. The pH sensor maintains an error below 2% within the ideal range of 5.5-6.5. The system supports automatic and manual pump control. QoS evaluation of MQTT communication showed stable performance with average throughput of 36.38 kbps (QoS 0), 2.54 kbps (QoS 1), and 1.55 kbps (QoS 2); delays of 762.68 ms, 1053.3 ms, and 1433.12 ms; and jitter of 26.91 ms, 28.44 ms, and 35.62 ms. Packet loss was 0% at all QoS levels, indicating reliable data transmission. Overall, the system improves monitoring accuracy and control efficiency, offering a practical solution for real-time automated hydroponic cultivation to support urban food security.